Bioactive compounds from Schisandra chinensis - Risk for aquatic plants? - Valíčková, Jana; Zezulka, Štěpán; Maršálková, Eliška; Kotlík, Josef; Maršálek, Blahoslav; Opatřilová, Radka (Aquatic toxicology (Amsterdam, Netherlands), 2023)
Schisandra chinensis is a potential plant for production of nutrient supplements due to adaptogens content. The dominant bioactive substance, lignan schisandrin, has positive effects on human health, but it can cause possible allelopathic effects in relation to other plants. S. chinensis is not native to European ecosystems, and its ecotoxicological properties have not been verified yet. Lemna minor was selected as a model aquatic plant to test its potential impact on the aquatic environment. Crude water extract from S. chinensis fruits, simulating the natural soaking of active substances in a surface water body, was used in treatments from 0.045 to 45 mg/L (according to the content of schisandrin as the dominating lignan). During seven days of cultivation, the growth (number of plants, leaf area, fresh weight) and photosynthetic activity of L. minor fronds were assessed. In low treatments (0.045 and 0.09 mg/L), the extract of S. chinensis did not cause any changes in duckweed growth parameters or photosynthetic performance. Higher treatments (0.45 and 0.9 mg/L) caused significant limitations in plants' number, total leaf area, and fresh weight. The photosynthetic parameters (basal chlorophyll fluorescence, quantum yields) were affected only by 0.9 mg/L. The highest treatment, 45 mg/L, exhibited extreme toxicity to duckweed plants causing their death during the first five days of cultivation. Schisandrin and other bioactive substances extractable from S. chinensis fruits can negatively impact water biota in the case of massive contamination of surface water.
Keywords: Water; Ecosystem; lignany; Schisandrin; Schisandra; Phytotoxicity; chemické látky znečišťující vodu; Lignans; Photosynthesis; voda; Lignan; Lemna minor; Humans; lidé; Adaptogen; ekosystém; Water Pollutants, Chemical